2019
DOI: 10.1039/c9ta08379k
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the controversial catalytic active sites of Co3O4 for the oxygen evolution reaction

Abstract: Controversial results still exist about the activities of tetrahedral (Co2+) and octahedral (Co3+) sites in Co3O4 toward the OER. Theoretical and experimental data confirm that octahedral sites are responsible for the OER, using model catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 48 publications
3
88
0
1
Order By: Relevance
“…When Co 3 O 4 is added to the heterostructure, a similar phenomenon of decreasing the overpotential is reported. [39] Hydrous NiMoO 4 helps in strengthening the electrochemical performances due to its high concentrations of active surface sites, and defective or "cracked" morphology, while cobalt decreases the overpotential due to the increase of the electrical conductivity (lower R ct ), which will be confirmed by the valence band measurement later. As a result, the overall performance improvement is associated with the synergistic effect of both hydrous NiMoO 4 and Co 3 O 4 electrocatalysts.…”
Section: Electrochemical Characterizationsmentioning
confidence: 70%
“…When Co 3 O 4 is added to the heterostructure, a similar phenomenon of decreasing the overpotential is reported. [39] Hydrous NiMoO 4 helps in strengthening the electrochemical performances due to its high concentrations of active surface sites, and defective or "cracked" morphology, while cobalt decreases the overpotential due to the increase of the electrical conductivity (lower R ct ), which will be confirmed by the valence band measurement later. As a result, the overall performance improvement is associated with the synergistic effect of both hydrous NiMoO 4 and Co 3 O 4 electrocatalysts.…”
Section: Electrochemical Characterizationsmentioning
confidence: 70%
“…Very recently, the Yao group revisited Co 3 O 4 to identify its real catalytic active sites by comparing Co 3 O 4 exhibiting the same morphology but with various ratios of Co 2+ Td and Co 3+ Oh sites via a combination of experimental and DFT calculations. [ 87 ] Specifically, the calculated overpotential was 290 mV for Co 3 O 4 hexagonal platelets with the (110)‐B plane containing only Co 3+ Oh on the surface that was significantly smaller than that of the (111) plane exposed with only Co 2+ Td (790 mV); this result demonstrated that Co 3+ Oh might act as the active site in Co 3 O 4 for water oxidation.…”
Section: High‐valence Metal Sitesmentioning
confidence: 99%
“…The OER intermediates, OH, O and OOH, were placed atop the two most catalytically active adsorption sites -Co oct and Co tet (Fig. 2) on both terminating planes (Xu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%